2023
DOI: 10.3389/fmed.2023.1100547
|View full text |Cite
|
Sign up to set email alerts
|

The cut-off value for HOMA-IR discriminating the insulin resistance based on the SHBG level in women with polycystic ovary syndrome

Abstract: IntroductionThe study aimed to estimate the cut-off value for homeostatic model assessment for insulin resistance (HOMA-IR) discriminating the insulin resistance based on the sex hormones binding globulin (SHBG) level in women with polycystic ovary syndrome (PCOS).Materials and methodsData from medical records of 854 Caucasian women diagnosed with PCOS were analyzed. Anthropometric data, fasting plasma glucose, insulin and SHBG levels were measured. HOMA-IR was calculated with a standard formula. The cut-off v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Insulin resistance associated with PCO improves with appropriate treatment of the disease; however, in addition to the classical OGTT measurement, a simple parameter that correlates well with the daily changes of serum insulin levels would be helpful to monitor long term changes of carbohydrate metabolism. Based on the literature data, SHBG seemed to be a promising parameter, as an inverse linear correlation between HOMA index and SHBG was seen in some patients with PCO syndrome [18][19][20], while others did not suggest it as a marker in PCO syndrome due to the excessive variability of SHBG [21]. In the current investigation, we aimed to determine whether an inverse linear correlation could also be seen in women with normal fasting insulin, accompanied by normal/low body weight phenotype PCO syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance associated with PCO improves with appropriate treatment of the disease; however, in addition to the classical OGTT measurement, a simple parameter that correlates well with the daily changes of serum insulin levels would be helpful to monitor long term changes of carbohydrate metabolism. Based on the literature data, SHBG seemed to be a promising parameter, as an inverse linear correlation between HOMA index and SHBG was seen in some patients with PCO syndrome [18][19][20], while others did not suggest it as a marker in PCO syndrome due to the excessive variability of SHBG [21]. In the current investigation, we aimed to determine whether an inverse linear correlation could also be seen in women with normal fasting insulin, accompanied by normal/low body weight phenotype PCO syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several publications on the relationship between insulin sensitivity (the HOMA index) and serum SHBG levels. Studies have demonstrated an inverse linear correlation between the Homeostasis Model Assessment (HOMA) index and SHBG, which makes SHBG a suitable marker for metabolic characterization [18][19][20]. However, there has also been research that has not recommended the use of SHBG as a marker in PCO syndrome due to its high variability [21].…”
Section: Of 10mentioning
confidence: 99%
“…A reduction in the SHBG concentration, a globulin produced mainly in the liver, is associated with PCOS and is a marker of the severity of hepatic insulin resistance. The expression of SHBG mRNA was found to be negatively correlated with the accumulation of triglycerides in hepatocytes [ 53 ]. ALT, a marker of liver cell injury, was elevated above 19 IU/mL in 35.7% of Low HDL-C subfertile women as compared with 4% of fertile women with a level of HDL-C above 50 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…The Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) is an easy and non-invasive way to figure out how sensitive your body is to insulin [ 24 ]. The PCOS patients were classified as insulin resistant (HOMA IR ≥ 2.0, n = 35) or non-insulin resistant (HOMA IR < 1.9, n = 27) using the Homeostasis Model Assessment of Insulin Resistance (HOMA IR) [ 25 ]. If the value is greater than 2.0, it suggests that a person’s body might be resistant to insulin.…”
Section: Methodsmentioning
confidence: 99%